A focus groups study of staff team experiences of providing interdisciplinary rehabilitation for people with dementia and their caregivers—a co-creative journey - Nina Lindelöf; Ingeborg Nilsson; Håkan Littbrand; Yngve Gustafson; Birgitta Olofsson; Anncristine Fjellman-Wiklund (BMC Geriatrics, 2023)
Abstract Background The World Health Organization claims that rehabilitation is important to meet the needs of persons with dementia. Rehabilitation programmes, however, are not routinely available. Person-centred, multidimensional, and interdisciplinary rehabilitation can increase the opportunities for older adults with dementia and their informal primary caregivers to continue to live an active life and participate in society. To our knowledge, staff team experiences of such rehabilitation programmes, involving older adults with dementia and their informal caregivers has not been previously explored. Methods The aim of this qualitative focus group study was to explore the experiences of a comprehensive staff team providing person-centred multidimensional, interdisciplinary rehabilitation to community-dwelling older adults with dementia, including education and support for informal primary caregivers. The 13 staff team members comprised 10 professions who, during a 16-week intervention period, provided individualised interventions while involving the rehabilitation participants. After the rehabilitation period the staff team members were divided in two focus groups who met on three occasions each (in total six focus groups) and discussed their experiences. The Grounded Theory method was used for data collection and analysis. Results The analysis resulted in four categories: Achieving involvement in rehabilitation is challenging, Considering various realities by acting as a link, Offering time and continuity create added value, and Creating a holistic view through knowledge exchange, and the core category: Refining a co-creative process towards making a difference. The core category resembles the collaboration that the staff had within their teams, which included participants with dementia and caregivers, and with the goal that the intervention should make a difference for the participants. This was conducted with flexibility in a collaborative and creative process. Conclusions The staff team perceived that by working in comprehensive teams they could provide individualised rehabilitation in creative collaboration with the participants through interaction, knowledge exchange, time and continuity, coordination and flexibility, and a holistic view. Challenges to overcome were the involvement of the person with dementia in goal setting and the mediating role of the staff team members. The staff pointed out that by refinement they could achieve well-functioning, competence-enhancing and timesaving teamwork.